2020
DOI: 10.1097/pr9.0000000000000853
|View full text |Cite
|
Sign up to set email alerts
|

The Delaware Pain Database: a set of painful expressions and corresponding norming data

Abstract: Supplemental Digital Content is Available in the Text. We present a fully characterized face stimulus database focusing on expressions of pain, surpassing previous sets in terms of size, quality, diversity, and characterization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 82 publications
(109 reference statements)
0
29
0
Order By: Relevance
“…Emotion expressions were created following procedures detailed in the Delaware Pain Database (Mende-Siedlecki et al, 2020). In Experiment 1, participants saw six Black and six White targets making six different expressions of pain and anger.…”
Section: Methodsmentioning
confidence: 99%
“…Emotion expressions were created following procedures detailed in the Delaware Pain Database (Mende-Siedlecki et al, 2020). In Experiment 1, participants saw six Black and six White targets making six different expressions of pain and anger.…”
Section: Methodsmentioning
confidence: 99%
“…The stimulus materials (ie, avatars) were taken from the empirically validated Delaware Pain Database (DPD 29 ). To create these stimuli, photographs were taken of real Black and White adult faces (age range: 18-35 years).…”
Section: Methodsmentioning
confidence: 99%
“…We selected 12 avatars that did not differ on social evaluations, latent emotional content, and demographic features (apart from their perceived race and gender). 29…”
Section: Methodsmentioning
confidence: 99%
“…Further, there are some limitations with UNBC-McMaster, such as the small number of participants (subjects) which may lead to a database bias problem. Movement also varies across subjects during pain stimulation, and their faces are sometimes partially occluded and this represents potential confounds in experimental designs [27]. Gruss et al [28] reported significant progress in automated pain assessment when using biopotential data.…”
Section: Related Workmentioning
confidence: 99%